Changes in the health of mothers of children with neurodevelopmental disabilities: An administrative data study. (March 2019) - Arim, Rubab G.; Miller, Anton R.; Kohen, Dafna E.; Guèvremont, Anne; Lach, Lucy M.; Brehaut, Jamie C.
Abstract: Background: Using linked administrative health data, this study compared the health and healthcare service utilization between mothers of children with and without neurodevelopmental disabilities (NDD), before, during, and after the birth of a child. Methods: The population ( N  = 25, 388) was based on a cohort of children born in 2000 and who were, along with their mothers, continuously registered with the British Columbia's universal health insurance program between 2000 and 2007. Results: Compared to mothers of children without NDD, mothers of children with NDD were more likely to have chronic conditions and higher service utilization before child birth. Mothers of children with NDD showed a smaller increase in physician visits in the year before birth but a greater increase in different prescription drugs in the year after birth. There was no further divergence (or convergence) in health and service utilization between the groups in the 7-year period post-birth. Conclusions: Differences in health and healthcare service utilization between mothers of children with and without NDD existed before the birth of the child and did not diverge in the 7 years post-birth. Replication of these findings is warranted as well as follow-up analyses examining longer term outcomes for mothers beyond 7 years post-birth.